Impact of selenium nanoparticles on plant stress tolerance: a comprehensive review - Arivalagan, Gomathi; Das, Utpal (Frontiers in Nanotechnology, 2026)
Selenium (Se), initially perceived mostly as a harmful element, is now recognised as an effective trace nutrient that promotes plant growth and stress resilience. Though not vital for most plant species, adequate Se concentrations may increase photosynthesis, activate antioxidant defence mechanisms, and improve tolerance to various biotic and abiotic stressors. The application of selenium nanoparticles (SeNPs) has been proposed because they exhibit greater bioavailability, higher stability, and lower toxicity compared to inorganic selenium forms, and recent advances in nanotechnology have enabled their efficient synthesis. SeNPs are readily internalised by plants, where they promote growth, regulate osmotic balance, activate stress-responsive genes, and strengthen plant defence mechanisms while minimising pollution. Current research highlights the role of Se and SeNPs in regulating redox homeostasis, secondary metabolite biosynthesis, and defence signalling networks. This review synthesises recent findings on Se speciation, uptake pathways, metabolic incorporation, and the diverse physiological roles of SeNPs in improving crop resilience. Future studies must rely on clarifying the molecular mechanisms, determining optimal application strategies, and integrating SeNPs into sustainable agricultural practices to enhance productivity and stress tolerance, thereby addressing concerns over food security under the impacts of climate change.